Peranan bahasa dalam pembinaan insan dan pembangunan masyarakat hadhari - Awang Sariyan (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2009)
Since early human live, beginning with Prophet Adam a.s., language has played very significant role in developing the concept of oneself, and concept of acquiring knowledge. Later on, in the process of developing human civilization, language become very important element in shaping the world view of a community, conceptualizing the philosophy, knowledge and thinking process, and generating huJurnal man creativities in every aspect of their life. Muslim scholars such as al-Ghazali and al-Farabi, and western thinkers such as Humboldt, Descartesm, Wittgenstein and Chomksy acknowledge language as society, language should be placed in proper position in human live. This articles describes the importance of language in the develoment of human live and society, and proposes practical methods toward its realisation.